KULTUR PAKAN ALAMI SPIRULINA PLATENSIS PADA SKALA LABORATORIUM: Natural Feed Culture of Spirulina platensis on Laboratory Scale - Nursadilah, Nursadilah; Rahmadani, Thoy Batun Citra (Ganec Swara, 2025)
Spirulina platensis microalgae is a nutrient-rich natural food source with high potential for laboratory-scale development. This study aims to determine the growth of Spirulina platensis in laboratory-scale culture and the water quality parameters that support it. Observations were made on the density of Spirulina platensis and water quality including temperature and salinity. The results showed that Spirulina platensis experienced a lag phase on days 0 to 4 with a density of 72,356–184,713 units/mL, then entered the exponential phase on days 5 to 8 with a density reaching 1,601,910 units/mL. Temperature conditions during the study ranged from 23–25°C and salinity was stable at 15 ppt, which is still within the optimal range for Spirulina platensis growth. The use of KW21 fertilizer has been proven to support the optimal growth of this microalgae because it contains complete macro and micro nutrients. Overall, Spirulina platensis culture at laboratory scale showed good growth and can be used as a starting stock for the development of semi-mass scale culture.